Network‐targeted approach and postoperative resting‐state functional magnetic resonance imaging are associated with seizure outcome. Issue 3 (11th July 2019) - Boerwinkle, Varina L.; Cediel, Emilio G.; Mirea, Lucia; Williams, Korwyn; Kerrigan, John F.; Lam, Sandi; Raskin, Jeffrey S.; Desai, Virendra R.; Wilfong, Angus A.; Adelson, P. David; Curry, Daniel J.
Abstract : Objective: Postoperative resting‐state functional magnetic resonance imaging (MRI) in children with intractable epilepsy has not been quantified in relation to seizure outcome. Therefore, its value as a biomarker for epileptogenic pathology is not well understood. Methods: In a sample of children with intractable epilepsy who underwent prospective resting‐state seizure onset zone (SOZ)‐targeted epilepsy surgery, postoperative resting‐state functional MRI (rs‐fMRI) was performed 6 to 12 months later. Graded normalization of the postoperative resting‐state SOZ was compared to seizure outcomes, patient, surgery, and anatomical MRI characteristics. Results: A total of 64 cases were evaluated. Network‐targeted surgery, followed by postoperative rs‐fMRI normalization was significantly ( p < 0.001) correlated with seizure reduction, with a Spearman rank correlation coefficient of 0.83. Of 39 cases with postoperative rs‐fMRI SOZ normalization, 38 (97%) became completely seizure free. In contrast, of the 25 cases without complete rs‐fMRI SOZ normalization, only 3 (5%) became seizure free. The accuracy of rs‐fMRI as a biomarker predicting seizure freedom is 94%, with 96% sensitivity and 93% specificity. Interpretation: Among seizure localization techniques in pediatric epilepsy, network‐targeted surgery, followed by postoperative rs‐fMRI normalization, has high correlation with seizure freedom. This study shows that rs‐fMRI SOZ can be used as a biomarker of the epileptogenic zone, and postoperative rs‐fMRI normalization is a biomarker for SOZ quiescence. ANN NEUROL 2019;86:344–356